GAMBARAN PENGETAHUAN MASYARAKAT TENTANG SWAMEDIKASI PENGGUNAAN OBAT PENYAKIT KULIT DI RT 04 DESA GONDORUSO KECAMATAN PASIRIAN KABUPATEN LUMAJANG - Agnis Pondineka Ria Aditama (JURNAL ILMIAH FARMASI AKADEMI FARMASI JEMBER, 2023)
Skin disease is a disease that attacks the surface of the body caused by various causes such as fungi, bacteria and parasites. Skin diseases can be treated by self-medication.  The research location was carried out at RT 04 Gondoruso Village, Pasirian District. The aim of this research to know of describing skin disease self-medication in RT 04 of the Gondoruso village community. Data collection was carried out using a survey method and using a questionnaire as a data collection tool. The data collection procedure was carried out by giving questionnaires to respondents by visiting the respondent's house directly. This type of research is quantitative descriptive with 72 respondents. The instruments used in this study were questionnaires and data collection sheets (LPD). Based on the results of the study, it can be concluded that the description of the community in RT 04 Gondoruso Village, Pasirian District, Lumajang Regency shows good category knowledge about self-medication using skin disease drugs. This is shown from the percentage value of knowledge about skin diseases of 89.72% and about the use of drugs for skin diseases of 97,22% Keywords: Knowledge, Skin Disease, Self-medication.